Study of the effect of trebenides received from green tea Khmer and bacterial races - Meshal Alenezi; Omer Saeed; Manal Al-Haek (College of Education for Pure Sciences, 2007)
AbstractIn this study Triterpenoids have been extracted from green tea powder, after that it is action on two species of yeast Candida albicans and Candida tropicalis and two species of bacteria staphylococcus aureus and pseudomonas aeruginosa had been tested. This test shows variable degrees and effects, the growth of Candida albicans yeast has been inhibited 47% at a concentration of 12.5 µg/ml while the growth of Candida tropicalis has been inhibited by 43% at the same concentration while of 50 mg/ml pseudomonas aeruginosa had been inhibited by 66% and staphylococcus aureus by 58%at the same conc.الخلاصةفی هذا البحث تستخلص التربنویدات من مسحوق الشای الاخضر ثم یختبر تاثیرها فی نمو جنسین من الخمائر هما Candida albicans ، Candida tropicalis وجنسین من البکتریا هما staphylococcus aureus and pseudomonas aeruginosa وقد اظهرت درجات مختلفة من التاثیر اذ تثبط نمو خمیرة Candida albicans بنسبة 47%عند الترکیز5. 12 مایکروغرام/مل وتثبط نمو خمیرة Candida tropicalis بنسبة 43% عند الترکیز نفسه وتثبط نمو بکتریا pseudomonas aeruginosa بنسبة(66%) عند الترکیز 50 مایکروغرام /مل وتثبط نمو بکتریا staphylococcus aureus بنسبة 58% عند نفس الترکیز ولم یظهر ای تاثیر عند الترکیز 25 مایکروغرام /مل فما دون.